First records of two brackish gobiid genera (Teleostei: Gobiidae) from Taiwan as their western Pacific distributional addenda - Li, Hsien-En; Chen, I-Shiung (Zootaxa, 2025)
The ichthyofauna of brackish habitats from Taiwan is relatively unexplored due to collection difficulties and significant tidal activities. Here we provide detailed descriptions of two new generic and species records for Dotsugobius bleekeri (Popta, 1921) and Mangarinus waterousi Herre, 1943. Predorsal region of both gobiids is naked entirely. Based on external morphologies, Dotsugobius bleekeri can be characterised by possessing a stout body with a somewhat teardrop-shaped lateral profile and reddish-brown body with numerous transverse creamy yellow stripes and two creamy yellow stripes under eye; Mangarinus waterousi can be characterised by having an elongate body, an oval-shaped caudal fin with a spear-shaped tip and uniformly dark brown or black body with 2 white transverse bands on anterior part of trunk and caudal peduncle. Detailed redescriptions of these two gobiids are given, with further discussions of their sympatric species and ecology patterns.